Violência obstétrica e os impactos na saúde mental materna - Lopes, Esther Flora Riguetto (Universidade Federal de São Carlos, 2022)
This is a qualitative approach study, developed in the intervention research modality, which had the purpose of understanding the obstetric violence impacts in the maternal health scope, identifying possible connections between the obstetric violence and the psychic suffering of women victims of this violence. For that, an online questionnaire publicized using the snowball sampling and the results of a focal group with 7 respondent women were used as data production techniques. Results: the analyzed narratives will be presented in 3 categories: the obstetric violence description from the participants' perceptions about that violence; the obstetric violence impacts in the women’s mental health; the obstetric violence resonances or effects in the women’s daily life. The study concludes that it is possible to identify violence obstetric impacts in the women’s mental health, from both the psych suffering and the trauma, symptoms and mental disorders development; as well as that the violence experiences can negatively affect the after birth activities, the motherhood and, even, a future motherhood perspective.
Obstetric violence and the impacts on maternal mental health
Keywords: Violência obstétrica; Saúde mental; Saúde da mulher; Obstetric violence; Mental health; Women’s health; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL